Early antithrombotic and anti-inflammatory effects of simvastatin versus fenofibrate in patients with hypercholesterolemia - Undas, Anetta; Celinska-Löwenhoff, Magdalena; Domagala, Teresa B.; Iwaniec, Teresa; Dropinski, Jerzy; Löwenhoff, Tomasz; Szczeklik, Andrew (Thrombosis and Haemostasis, 2005)
The aim of the study was to determine whether a short-term treatment with simvastatin or fenofibrate may result in beneficial anti-inflammatory and antithrombotic effects in patients with high risk of coronary artery disease. In a randomized, double-blind study, we compared markers of inflammation, thrombin formation and platelet activation in patients with LDL cholesterol >130 mg/dl assigned to receive simvastatin (40 mg/d; n=20) or micronised fenofibrate (160 mg/d; n=22) for 28 days. Simvastatin, but not fenofibrate, lowered C-reactive protein (CRP) by 32% on day 3 (p<0.001), while both drugs reduced CRP significantly on day 28. Interleukin-6, soluble CD40 ligand, and monocyte chemoattractant protein-1 levels decreased significantly (by 20 to 50%) in both treatment groups on days 3 and 28. Soluble cell adhesion molecules remained unchanged in both groups. Simvastatin and fenofibrate significantly lowered plasma concentrations of thrombin-antithrombin complexes on days and 28, but not platelet β-thromboglobulin (βTG) levels. Soluble P-selectin was lowered only in the simvastatin group. The total amount of thrombin generated at the site of microvascular injury also declined (by about 30%) as early as after 3 days of fenofibrate or simvastatin therapy, whereas βTG release was reduced only in the simvastatin group on days 3 and 28.All the effects were independent of the changes in lipid profiles. Our results suggest that statins and fibrates can exert antithrombotic and anti-inflammatory effects as early as after 3 days of therapy. However, in contrast to statins, fibrates have no influence on platelet function within one month of therapy.
Keywords: Statins; fibrates; cholesterol; coagulation; inflammation